The Observationes tumultuariae of Johan van Bleiswijk (1684-1748) - Sirks, Boudewijn, (Early Modern History and Modern History E-Books online, Collection 2026., 2026)
In the Dutch Republic, courts made decisions by voting and judgments were not given reasoned motivations. Although some judges kept a record of the preceding deliberations, the only extensive collections we have had until recently from the eighteenth century are those of van Bijnkershoek and Pauw. Fortunately, we are also in possession of the Observationes of Johan van Bleiswijk (in 1723-1748 a colleague of van Bijnkershoek). Van Bleiswijk provides an overview of the various opinions relating to cases at the time, but also expounds on his own views. In this way, he sheds light on his own perspective and legal views. Hence, van Bleiswijk's Observationes are a most welcome addition to our knowledge of judicial decision-making in the Dutch Republic.